Development of Raman spectral markers to assess metastatic bone in breast cancer - Ding, Hao (Society of Photo-Optical Instrumentation Engineers, 2014)
Bone is the most common site for breast cancer metastases. One of the major complications of bone metastasis is pathological bone fracture caused by chronic bone loss and degeneration. Current guidelines for the prediction of pathological fracture mainly rely on radiographs or computed tomography, which are limited in their ability to predict fracture risk. The present study explored the feasibility of using Raman spectroscopy to estimate pathological fracture risk by characterizing the alterations in the compositional properties of metastatic bones. Tibiae with evident bone destruction were investigated using Raman spectroscopy. The carbonation level calculated by the ratio of carbonate/phosphate [Formula: see text] significantly increased in the tumor-bearing bone at all the sampling regions at the proximal metaphysis and diaphysis, while tumor-induced elevation in mineralization and crystallinity was more pronounced in the metaphysis. Furthermore, the increased carbonation level is positively correlated to bone lesion size, indicating that this parameter could serve as a unique spectral marker for tumor progression and bone loss. With the promising advances in the development of spatially offset Raman spectroscopy for deep tissue measurement, this spectral marker can potentially be used for future noninvasive evaluation of metastatic bone and prediction of pathological fracture risk.